STEELMAKING OF RUP “BMZ” IN DYNAMICS OF 20 YEARS - V. A. Matochkin; V. V. Enders; M. P. Gulajev; V. Ju. Gunenkov (Литьë и металлургия)
In conditions of RUP “BMZ” for the first time in practice of electric steelification in USSR in production quantities the new conception of melting of high level in blast steel-melting furnace has been embedded. The different variants of the out-of furnace processing and deoxidation of cord steel are tested.